ANALISIS STRATEGI PENGEMBANGAN DESTINASI WISATA PUNCAK KABUN PALANTA INYIAK REDA SINGGALANG KABUPATEN AGAM DALAM MENINGKATKAN KUNJUNGAN WISATAWAN - Kiki Marliza; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2024)
The absence of human resources and tourism, the underdevelopment of Puncak Kabun Palanta Inyiak Reda Singgalang tourism, the poor quality of the roads leading to tourist sites, and the poor quality of public amenities such restrooms and prayer rooms are the main research topics in this thesis. The purpose of this study is to ascertain the best course of action for enhancing Puncak Kabun Palanta Inyiak Reda Singgalang as a tourist destination in the Agam Regency in order to attract more visitors. In this study, the author used a qualitative descriptive method. Three methods are utilized to acquire data: documentation, interviews, and observation. SWOT, IFE, and EFE analyses, SWOT diagrams, and SWOT matrices are the power analysis techniques that are employed. The results of the research show that the Puncak Kabun Palanta Inyiak Reda Singgalang tourist destination already has strengths in Internal Factors, but has not been able to maximize opportunities originating from External factors because there are various threats that are quite hindering. Therefore, diversification must be carried out so that there can be development in tourist areas and tourism renewal that provides innovation as well as security and comfort in the Puncak Kabun Palanta Inyiak Reda Singgalang tourist destination.